Valorization of Cork Waste to Improve the Anti-Corrosion Properties of Concrete Reinforcements - Belkhir, S.; Bensabra, H.; Chopart, J. P. (Corrosion Science and Technology, 2022)
Corrosion of steel reinforcement is the most important mode of concrete structures damages. It strongly depends on the composition and physicochemical properties of the cementitious medium. The use of waste materials as lightweight aggregates in concrete is environmentally recommended in polluted environments such as marine and/or industrial atmospheres in order to reduce its porosity and ensure the requested protection of reinforcing steel. The present study investigated the effect of waste cork addition on corrosion resistance of steel rebar in mortar specimen prepared in the laboratory. The main objective of this study was to improve the corrosion resistance of reinforcing steel. Another objective of this study was to valorize this ecological product and preserve the environment. Results obtained from various electrochemical tests indicated that the presence of a fine cork powder substantially improved the corrosion resistance of steel in the mortar contaminated by chloride ions. This improvement was reflected by a notable decrease in corrosion current density and a shift of corrosion potential of the steel towards more noble values. Moreover, the presence of a fine cork powder in the mortar had no adverse effect on its mechanical properties.